Analysis of elemental and isotopic variation in glass frictionators from 0.22 rimfire primers. (December 2018) - Seyfang, Kelsey E.; Kobus, Hilton J.; Popelka-Filcoff, Rachel S.; Plummer, Andrew; Magee, Charles W.; Redman, Kahlee E.; Kirkbride, K. Paul
Highlights: Glass frictionator present in 0.22 rimfire primers can be detected in GSR. Elemental variations in the glass can be exploited for GSR case investigations. A inter-brand discrimination power of over 90% has been calculated using ToF-SIMS. Abstract: The majority of 0.22 calibre rimfire ammunition available in Australia, and overseas, tends to use glass powder rather than antimony sulfide frictionator in the primer. This glass can be the nucleus of a GSR particle, with other primer components condensing around and onto the glass structure. As the composition of glass frictionator remains largely unaltered during ammunition discharge[1] there is the possibility that frictionator composition could be used in GSR examinations to either correlate or discriminate between samples, thereby providing valuable information to an investigation. In this study, the composition of glass frictionator from a wide variety of ammunition was analysed by time-of-flight – secondary ion mass spectrometry (ToF-SIMS), sensitive high-resolution ion microprobe (SHRIMP) and scanning electron microscopy – energy dispersive X-ray spectrometry (SEM-EDS). Refractive index (RI) was measured using glass refractive index measurement (GRIM). Across the population of ammunition studied, it was found that the elemental and isotopic composition of frictionator varied. ToF-SIMS was able to discriminate 94.1% of brands in a pairwise comparison and SEM-EDS achieved a pairwise discrimination power of 79.4%. If SHRIMP was combined with the other two techniques, 95.6% of brands could be discriminated. Refractive index measurements supported the elemental data showing that there appeared, in most cases, to be only one population of glass within a cartridge. The results suggest that there is scope for frictionator analysis to contribute valuable, new capability to forensic GSR examinations.